Independent Learning in Higher Education: Perspectives and Challenges from EFL Students: Pembelajaran Mandiri di Pendidikan Tinggi: Perspektif dan Tantangan dari Mahasiswa Bahasa Inggris sebagai Bahasa Asing - Endah Luthfiyah; Sukarno (Language Development Center, 2025)
Background: In learning other language, higher education students’ perceptions of independent learning—including their motivations, challenges, strategies, and its impact on achievement—are crucial to investigate. Purpose: This research seeks to elucidate EFL students' motives, obstacles, tactics, and the effects of independent learning from their perspective. Method: A qualitative research design is used in this research. Data is collected through an open-ended questionnaire. The participants are ten first-year postgraduate students enrolled in the Higher Education Study Skills course. Then, open and selective coding are performed to analyse the data. Results and Discussion: The findings show different motivations from participants in their motivations, challenges, strategies, and impact from independent learning. This research also provides the mechanism on how the students manage their challenges to help them achieve learning goals. Various findings related to students’ perceptions invites contention among students. There are positive and negative impacts that come from independent learning. Conclusions and Implications: Revealing EFL higher students’ perspectives can be ended up by conclusion that there are some students’ socio background that can affect their perspectives. These findings implicate postgraduate students, lecturers, and future researchers to fill the blank information from the lecturers’ perspectives, different gender perspectives, or add more statistical data to support the newest research about independent learning in higher education level.